Clinical Instruments for the Verification and Differential Diagnosis of Post-Traumatic Stress Disorder and Traumatic Brain Injury in Combat Veterans - Smashna, Олена (Psychosomatic Medicine and General Practice, 2026)
The coexistence of post-traumatic stress disorder (PTSD) and mild traumatic brain injury (mTBI) represents a significant challenge among combat veterans due to the partial overlap of symptoms, which complicates differential diagnosis, treatment selection, and rehabilitation prognosis. The aim of this study was to evaluate the diagnostic value of the Boston Assessment of Traumatic Brain Injury – Lifetime (BAT-L) and the Clinician-Administered PTSD Scale (CAPS) in differentiating PTSD from the consequences of mTBI in military personnel, as well as to investigate the correlational relationships between the indicators of these instruments. Between 2015 and 2022, a comprehensive clinical and psychological assessment was conducted in 329 combat veterans seeking medical and psychological care. Participants were divided into three groups: PTSD (n=109), mTBI (n=112), and PTSD+mTBI (n=108). BAT-L was used for retrospective assessment of the severity, characteristics, and consequences of traumatic brain injury, while CAPS was applied for quantitative evaluation of PTSD symptoms across symptom clusters B–E. The results demonstrated that the highest BAT-L scores were observed in the mTBI group, the lowest in the PTSD group, and intermediate values in the PTSD+mTBI group. In the mTBI group, statistically significant correlations were identified between BAT-L scores and cognitive as well as emotional CAPS symptoms, indicating an association between injury severity and psychoemotional disturbances. In the PTSD+mTBI group, no statistically significant correlations were found, which may reflect the independent development of neurotraumatic and psychotraumatic symptom patterns. The findings support the necessity of a comprehensive approach to the assessment of veterans with PTSD, mTBI, and their comorbidity, enabling more accurate identification of therapeutic needs, development of integrated rehabilitation programs, and prediction of treatment outcomes. Keywords: PTSD, mild traumatic brain injury, veterans, BAT-L, CAPS, cognitive impairment, differential diagnosis. УДК: 616.89-008.454:616.83-001